Resilience and Vulnerability to Trauma: Early Life Interventions Modulate Aversive Memory Reconsolidation in the Dorsal Hippocampus - Couto-Pereira, Natividade de Sá; Lampert, Carine; Vieira, Aline dos Santos; Lazzaretti, Camilla; Kincheski, Grasielle Clotildes; Espejo, Pablo Javier; Molina, Victor Alejandro; Quillfeldt, Jorge Alberto; Dalmaz, Carla (Frontiers in Molecular Neuroscience, 2019)
Early life experiences program lifelong responses to stress. In agreement, resilience and vulnerability to psychopathologies, such as posttraumatic stress disorder (PTSD), have been suggested to depend on the early background. New therapies have targeted memory reconsolidation as a strategy to modify the emotional valence of traumatic memories. Here, we used animal models to study the molecular mechanism through which early experiences may later affect aversive memory reconsolidation. Handling (H) – separation of pups from dams for 10 minutes - or maternal separation (MS) – 3-hour separation - were performed from PDN1-10, using non-handled (NH) litters as controls. Adult males were trained in a contextual fear conditioning task; 24 hours later, a short reactivation session was conducted in the conditioned or in a novel context, followed by administration of midazolam 3 mg/kg i.p. (mdz), known to disturb reconsolidation, or vehicle; a test session was performed 24 hours after. The immunocontent of relevant proteins was studied 15 and 60 minutes after memory reactivation in the dorsal hippocampus (dHc) and basolateral amygdala complex (BLA). Mdz-treated controls (NH) showed decreased freezing to the conditioned context, consistent with reconsolidation impairment, but H and MS were resistant to labilization. Additionally, MS males showed increased freezing to the novel context, suggesting fear generalization; H rats showed lower freezing than the other groups, in accordance with previous suggestions of reduced emotionality facing adversities. Increased levels of Zif268, GluN2B, β-actin and polyubiquitination found in the BLA of all groups suggest that memory reconsolidation was triggered. In the dHc, only NH showed increased Zif268 levels after memory retrieval; also, a delay in ERK1/2 activation was found in H and MS animals. We showed here that reconsolidation of a contextual fear memory is insensitive to interference by a GABAergic drug in adult male rats exposed to different neonatal experiences; surprisingly, we found no differences in the reconsolidation process in the BLA, but the dHc appears to suffer temporal desynchronization in the engagement of reconsolidation. Our results support a hippocampal-dependent mechanism for reconsolidation resistance in models of early experiences, which aligns with current hypotheses for the etiology of PTSD.